KENAKALAN REMAJA AWAL DI LINGKUNGAN SEKOLAH DITINJAU DARI KETIDAKHADIRAN ORANG TUA KARENA MERANTAU - Aini, Siti Qorrotu (Jurnal Litbang: Media Informasi Penelitian, Pengembangan dan IPTEK, 2015)
ENGLISHEarly adolescent phase that coincided with the beginning of secondary school age have characteristics that emotionally still volatile because of the influence of hormonal changes in adolescents. This forms a distinctive characteristic in early adolescence which includes aspects social behavior, moral, religious, affective, cognitive and personality. The reviewed purpose is to explain the potential of early adolescent delinquency in the school environment on students whose parents migrated for temporary. Adolescent phase needs nurturing, guidance, direction and supervision. The parents roles is needed for the success of adolescent development. Adolescent who left by their parents for temporal migration have psychosocial youth impact in their school life. Adolescent beside studied academicly also required to comply with the applicable rules at school. Adolescent who are left for temporal migration and have psychosocial problem, forms of delinquency includes substance abuse such as alcohol, behavioral problems includes coming late, ditching, not doing homework, words are rude, alcohol, viewing pornography, fighting, courting school environment, write inappropriate words on the walls of the bathroom and indications brawl.Â INDONESIAFase remaja awal yang bertepatan dengan usia sekolah menengah memiliki karakteristik yang secara emosional masih bergejolak karena pengaruh perubahan hormonal dalam diri remaja. Hal ini membentuk karakteristik yang khas pada masa remaja awal yang meliputi aspek perilaku sosial, moral, religi, afeksi, kognitif dan kepribadian. Tujuan penulisan untuk menjelaskan potensi kenakalan remaja awal di lingkungan sekolah pada siswa yang orang tuanya merantau. Fase remaja membutuhkan pengasuhan, bimbingan, arahan dan pengawasan. Peran orang tua sangat dibutuhkan untuk keberhasilan perkembangan anak remaja. Remaja yang ditinggal orang tuanya merantau memiliki dampak psikososial remaja dalam kehidupannya bersekolah. Remaja, selain belajar secara akademis juga dituntut untuk mematuhi aturan yang berlaku disekolah. Remaja yang ditinggal merantau dan memiliki masalah psikosial, bentuk-bentuk kenakalannya meliputi penyalahgunaan zat berupa minuman keras, masalah perilaku meliputi terlambat, membolos, tidak mengerjakan tugas/PR, perkataan yang kasar, minuman keras, melihat pornografi, berkelahi, pacaran dilingkungan sekolah, menulis kata-kata tidak pantas di tembok kamar mandi dan indikasi tawuran.